Examining the use of implementation science in autism intervention research: A scoping review. - Lee, James D.; Terol, Adriana Kaori; Tschida, Jessica E.; Pomales-Ramos, Anamiguel; McEathron, Scott; Wallisch, Anna; A Boyd, Brian (Autism: The International Journal of Research & Practice, 2025)
Although the field of autism intervention has strived to identify evidence-based practices, translating these interventions into real-world settings remains a significant challenge. This gap particularly impacts marginalized communities, where access to and quality of services are often inferior. Implementation science addresses these gaps by promoting the adoption and integration of evidence-based practices in community-based settings, thereby helping reduce disparities. While various frameworks and strategies have emerged to guide the successful implementation of autism evidence-based practices, the application of implementation science within autism intervention research remains underexplored. To address this gap, we conducted this scoping review that included 13 studies to examine how implementation science is applied in autism intervention research delivered in community-based settings. Specifically, we aimed to (1) describe the characteristics of implementation-focused studies (e.g. study design, participant types, intervention contexts); (2) examine how implementation frameworks, strategies, and outcomes were used to guide and evaluate intervention efforts; and (3) analyze how studies align with phases of the autism-specific implementation framework developed by Boyd et al. (Autism). Most studies were conducted in school settings. Fidelity was the most frequently assessed implementation outcome, while acceptability, adoption, and appropriateness were also commonly measured. Nearly all studies focused on early-phase implementation (e.g. exploration, initial implementation), with limited attention to sustainment or scale-up. The findings offer a starting point for future research to better implement autism evidence-based practices in community settings. This study looks at ways to improve how autism support programs are used in everyday community settings like schools and clinics. These programs are approaches that research has shown can help autistic individuals develop important skills, such as communication, social interaction, and managing behavior. Many of these are psychosocial programs, which means they focus on emotional, social, and behavioral support rather than medication or medical treatment. However, there is a challenge in implementing these interventions in real-world settings, especially in marginalized communities where services are often lacking or lower in quality. The field of implementation science helps bridge this gap by guiding and encouraging the use of evidence-based practices in community settings, aiming to reduce disparities. To better understand this, we did a scoping review that included 13 studies that used implementation science to support autism interventions. We looked at what types of strategies were used, how success was measured, and how well the programs fit into the communities where they were used. Most of the studies took place in schools and involved teachers, school staff, or caregivers of autistic children—altogether including data from 3488 participants. These studies tested different programs to improve outcomes of autistic individuals, such as social skills, communication, and behavior in schools.